2006
DOI: 10.1016/j.jbankfin.2005.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of international stock and bond market integration: Influence of the European Monetary Union

Abstract: This paper examines the dynamic relationship between daily stock and government bond returns of selected countries over the past decade to infer the state and progress of interfinancial market integration. We proceed to empirically investigate the influence of the European Monetary Union (EMU) on time-variations in inter-stock-bond market integration/segmentation dynamics using a two-step procedure. First, we document the downward trends in time-varying conditional correlations between stock and bond market re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
129
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(156 citation statements)
references
References 36 publications
17
129
3
2
Order By: Relevance
“…The authors find a strong connection between stocks and bonds during crash-rebound episodes: immediately after the crash investors sell their risky bonds, and after the rebound they sell some of their safest bonds (usually government) to buy back the risky ones. Kim et al, (2006) continued a previous study of Connolly et al, (2005) who found that the future stockbond correlation at higher daily frequency decreases with increasing stock market uncertainty, concluding that this is influenced by the flight-to-quality phenomenon. The authors also found that stock-bond market integration moved to zero and even negative mean levels in most countries, consistently with flight-to-quality.…”
Section: Literature Reviewsupporting
confidence: 76%
See 3 more Smart Citations
“…The authors find a strong connection between stocks and bonds during crash-rebound episodes: immediately after the crash investors sell their risky bonds, and after the rebound they sell some of their safest bonds (usually government) to buy back the risky ones. Kim et al, (2006) continued a previous study of Connolly et al, (2005) who found that the future stockbond correlation at higher daily frequency decreases with increasing stock market uncertainty, concluding that this is influenced by the flight-to-quality phenomenon. The authors also found that stock-bond market integration moved to zero and even negative mean levels in most countries, consistently with flight-to-quality.…”
Section: Literature Reviewsupporting
confidence: 76%
“…The preferred maturity is 10 years: according to (Baur & Lucey, 2006), long term government bonds should be selected over short term government bonds because they can be considered as closer maturity substitutes to stocks and monetary policy operations are more likely to have an unclear influence on short-term rather than on long-term government bonds. The same opinion is held by (Kim et al, 2006). (Li, 2002;Andersson et al, 2004) and other authors use 10 year government bond indices as the most appropriate for comparison with stocks.…”
Section: Source: Compiled By the Authors Based On Thomson Reuters Andmentioning
confidence: 90%
See 2 more Smart Citations
“…The studies that connect the convergence literature to non-economic growth indicators, such as health expenditures, financial markets and tourism, were performed by Brada et al (2005); Kim et al (2005Kim et al ( , 2006; Narayan (2007);Fung (2009);Eun and Lee (2010); Su et al (2010); Narayan et al (2011) andPark et al (2015).…”
Section: Motivation For Ict Convergencementioning
confidence: 99%